Fuel Cell Emulator with MPPT Technique and Boost Converter - Maaspaliza Azri; Nur Hidayah Abu Khanipah; Zulkifilie Ibrahim; Nasrudin Abd. Rahim (Institute of Advanced Engineering and Science, 2017)
This paper presents the simulation between fuel cell model and interleaved DC-DC boost converter (IBC) using a constant voltage maximum power point tracking (MPPT) technique. The main advantage of this method is it had the simplest algorithm and can be computed for the high efficiency IBC. The MPPT technique forces the fuel cell to meet the maximum power that the fuel cell can generate. To test the IBC along with the MPPT algorithm, MATLAB/Simulink simulation is carried out. This MPPT method increases the efficiency of power delivered from the fuel cell. The IBC has also chosen for its advantages of reduction of passive component's size, as well as reduced the current ripple that could affect the fuel cell stack. It is envisaged that the MPPT method of constant voltage gives a handful of help in designing a low cost and high efficient fuel cell system along with the interleaved boost converter chosen